A Radical Awakening : Turn Pain into Power, Embrace Your Truth, Live Free - Shefali, Dr. (London Yellow Kite, 2021)
The New York Times bestselling author and renowned clinical psychologist teaches women how to transcend their fears and illusions, break free from societal expectations, and rediscover the person they were always meant to be: fully present, conscious and happy.
Include Index
Keywords: Self-actualization (Psychology) in women -- Self-realization in women